(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The phenomenon of urbanization is neither new norsurprising. During the ages people have tended to cluster together for theirliving and in due course of time areas in habited by human beings for purposesother than agriculture got designated as urban. Of course, invariably there areother attributes too but these are in the nature of afterthoughts andrefinements, and mainly to distinguish the viable units from the non-viableones and do not deserve to be considered as characteristic of the scene. Onemay, indeed, be tempted to make a broad generalization to help identification;clusters where human beings are found together basically and initially forpurely social reasons maybe termed as non-urban; areas where economic necessitybrings them together are generally urban. That is so far as sociologicalfactors go too. Naturally, with the evolution of human society and complexitiesadded to human activity, even the rural areas have gradually begun to gettransformed into economic entities. Agriculture has already become an industryin many countries and is well on its way to show these characteristics in Indiaas well. A way of life is getting changed to a way of living. Consequentchanges in social habits, family and institutional relationships and thepredominance of economic attitudes and pressures are already abundantlyvisible. All this is profoundly disturbing to the romantic view of humansociety, but is undoubtedly a blessing in the present stage of human evolution.Thanks to the unabashed maintained of double standards, the human element inthe rural areas was relegated into the background and treated with apathy, ifnot contempt undeserving in the eyes of the urban dweller of the good things oflife. The producer of milk and food and vegetables had become a second classcitizen, whereas the manufacturer of pins and needles in the miserable slums ofan urban area was the better citizen! Naturally, such a state of affairs couldnot last indefinitely and the exodus to towns from the rural areas began manydecades ago. In some countries, the saturation-point has been reached already.In India the process continues unabated though the magnitude of the problem isnot fully realised everywhere for various reasons.